RELIGIOUS RADICALISM IN THE PERSPECTIVE OF ISLAMIC LAW - Fina Zuhaida; Zara Wanda; Risqi Arfiyanto; Aufa Zulfa Almira (Islamic Studies Journal for Social Transformation, 2024)
The phenomenon of religious radicalism is a serious challenge in religious, national, and state life. Radicalism not only disrupts social stability, but also tarnishes the image of peaceful and tolerant religious teachings, especially Islam. This article aims to examine religious radicalism from the perspective of Islamic law, by tracing the ideological roots, forms of manifestation, and the views of sharia on radical actions. With a qualitative approach and literature study, this study found that Islamic law firmly rejects all forms of violence that damage the order of society, even if carried out in the name of religion. Islam as a religion of rahmatan lil 'alamin upholds the values of justice, tolerance, and peace. Therefore, radicalism cannot be justified according to sharia because it is contrary to maqashid al-syari'ah and the principle of moderation (wasathiyah) in Islam.